EL FENÓMENO DROGA EN LA POBLACIÓN ESCOLAR DE LA PROVINCIA DE SAN JOSÉ: TIBÁS, 2000 - Obando Solano, Patricia (2001)
This study introduces some of the attitudes and characteristics related to drug abuse among primary school children, aged 9 to 15 years. The sample was drawn from all public schools located in Tibás county in San José.The results highlight an early age of onset for most of the drugs asked, especially for women. Significant differences in terms of drug use frequencies were found by school category (urban and suburban schools). Risk factors were determined by looking at the relationship between drug offer and drug abuse, and parental drug use. Protective factors such as religion and health information were relevant in this population.